(untitled) (CIPEEX, 2022)
SOCIAL INCLUSION CAN BE DEFINED AS A GROUP OF ACTIONS THAT AIMS TO INSERT AND GUARANTEE THE PARTICIPATION OF ALL IN SOCIETY, REGARDLESS OF SOCIAL CONDITION, ETHNICITY, SEXUAL ORIENTATION, PHYSICAL CONDITION, AMONG OTHERS. HIGHER EDUCATION INSTITUTIONS WERE ONCE SOMEWHAT LIMITED AND ELITIST, SINCE UNIVERSITIES DID NOT INVEST IN STRUCTURE FOR THE INTEGRATION OF PEOPLE WITH LIMITED PHYSICAL, AUDITORY, VISUAL AND MENTAL DISABILITIES, AS WELL AS CERTAIN MINORITIES SUCH AS THE BLACK, INDIGENOUS AND HOMOSEXUALS. IN RECENT YEARS THERE HAVE BEEN SEVERAL CHANGES IN BRAZILIAN HIGHER EDUCATION, PUBLIC INCLUSION POLICIES ARE AN EXAMPLE THAT ALLOWED THESE MINORITIES TO BE INSERTED IN BRAZILIAN UNIVERSITIES, BOTH PRIVATE AND PUBLIC. THUS, THIS WORK HAS THE OBJECTIVE OF UNDERSTANDING THROUGH DIDACTIC DEMONSTRATION, USING POSTERS AND MOCKUPS WITH PHRASES, DATA COLLECTED AT THE TEACHING INSTITUTION IN QUESTION AND IMAGES THAT ARE IMPACTING TO SHOW INFORMATION ABOUT THE MINORITIES AND DIVERSITY INCLUDED IN THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGLICA. RESULTS: IT IS HOPED TO PROMOTE GREATER AWARENESS OF THE SPECTATOR PUBLIC, CONSTITUTED IN ITS MAJORITY BY ACADEMIC OF THE COURSE OF DENTISTRY. CONCLUSION: IT IS OF GREAT IMPORTANCE TO HAVE A COMPREHENSIVE VIEW REGARDING INCLUSIVE PRACTICES IN THE UNIVERSITY ENVIRONMENT, INCLUDING THROUGH TESTIMONIES OF PEOPLE WHO SUFFER SOME BARRIER, WHICH IN A WAY LIMITS THEIR PARTICIPATION IN THE UNIVERSITY, SEEING THAT THESE BARRIERS DO NOT INCAPACITATE THEM, ON THE CONTRARY , MAKES THE PATH OF THESE PEOPLE MORE PROMISING. &NBSP; KEYWORDS:HIGHER EDUCATION. INCLUSION. MINORITIES